Contributos para a imagética decorativa dos recipientes cerâmicos da Idade do Ferro de Trás-os-Montes: entre a meseta e o litoral português - Pinto, Dulcineia (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2019)
The Iron Age containers’ representation includes all aspects related to containers; shapes, pastes, general aspect – surface treatments and color – and decoration. We intend here to make known, in a succinct way, the images and decorative aspect of the containers of the Crasto de Palheiros from the 9th century BC to the 2nd century AD. The decoration integrates the techniques and decorative organizations, the ways of making and the final results. We present the various decorative current that include comb and stamp decorated containers as well as other ways of decorating originated in local traditions.